Go/N ratio in tropical soils from Brazil - Rocha, Breno Padovezi; Pedrini, Rubens Antonio Amaral [UNESP]; Giacheti, Heraldo Luiz [UNESP] (My University, 2015)
The geotechnical behavior of tropical soils is complex and cannot be supported only by theclassical soil mechanics. The Standard Penetration Test (SPT) is broadly used for geotechnical sitecharacterization. However, it provides a single index to estimate several parameters. The seismicSPT is a test that associates the up-hole technique to the SPT. It allows determining the maximumshear modulus (Go) together with the N value. The ratio between Go determined from seismictests (cross-hole, down-hole, and SCPT) and the N value from SPT was used to identify unusualcompressibility of soils from three well studied sites from São Paulo State, Brazil. It was observedthat all studied soils presented a higher Go/N ratio than sedimentary uncemented sandy soils. Itwas also observed that the lateritic soils tend to achieve a higher Go/N ratio than the saproliticsoils. S-SPT tests were also carried out at the same studied sites and the use of the up-hole seismicdata and N value in the same test is an interesting approach to help characterize unusual anddifferent soil behavior based on Go/N ratio. Relating an elastic modulus to a penetration resistancecan help identifying different tropical soils since the low strain modulus determined by seismictests reflects the cemented structure of these soils.
Keywords: In situ testing; SPT; Seismic; up-hole; Tropical soils; Go/N ratio